UNDERPASS DALAM MANAJEMEN PEMBERITAAN MEDIA (Studi Deskriptif Kualitatif Tentang Manajemen Pemberitaan Kasus Underpass Makamhaji, Sukoharjo di Media Cetak Harian Umum Solopos dan Media Online Solopos.com Periode 1 Januari- 5 Maret 2013) - Nurjanah, Siti; Perwita, Alvika Hening; Herwindya, Sri (KOMUNITAS, 2013)
Solopos is the most existing press media in solo. Established in solo September 19thÂ 1997,inÂ thatÂ yearÂ soloÂ wasÂ aÂ cityÂ thatÂ hadÂ aÂ badÂ reputationÂ amongÂ press communities..Â RightÂ nowÂ SoloposÂ wasÂ expandingÂ itsÂ businessÂ byÂ creatingÂ new media,it was online version of Solopos, Solopos.com. achievement that had been achieved by Solopos.com in the last 6 months (Januari-Juni 2013) was getting the most visitors in solo regional,about 50.000-60000 visitors a day. All of Solopos andÂ Solopos.comÂ successÂ becauseÂ ofÂ supportedÂ byÂ goodÂ newsÂ management.Â In orderÂ toÂ seeÂ theÂ differencesÂ ofÂ newsÂ managementÂ ofÂ SoloposÂ andÂ Solopos.com, researcherÂ connectedÂ withÂ reportingÂ ofÂ underpass,Â planning,Â organizing, actuating and controlling. The study was conductedÂ in order to determine which news management applied in managing the news of Underpass. This research was a qualitative descriptive study. ResultsÂ fromÂ pressÂ mediaÂ managementÂ researchÂ inÂ newsÂ managementÂ of UnderpassÂ wasÂ doneÂ inÂ fourÂ stages,Â planning,Â organizing,Â actuatingÂ and controlling. In Planning Solopos.com was in the same side with Solopos butit was well planned because there was a planning meetingsÂ or editorial meeting every day at 15.00, all things were discussed in the meeting, such as headline proposals, andÂ theÂ selectionÂ of what theme wouldÂ beÂ written.Â MeetingÂ wasÂ attendedÂ byÂ all mediacandidates. Organizing the management reports on print media and online mediaÂ Solopos.comÂ hadÂ beenÂ formedÂ organizationalÂ structureÂ withitsÂ positions and duties. Actuating in management reporting begunwith the reporting process, reportingÂ wasÂ doneÂ byÂ theÂ sameÂ reporter,Â becauseÂ theÂ onlineÂ mediaÂ of Solopos.com didnât has it. This reporting was done by doing it right in the field, in MakamhajiÂ Sukoharjo.Â TheÂ newsÂ cameÂ oberÂ ofÂ theÂ rulesÂ ofÂ journalism. ControllingÂ inÂ managementÂ reportÂ wasÂ doneÂ byÂ editorsÂ thatÂ thetheÂ taskÂ was overseeing directly in the field issues (editor Solopos), overseeing incoming and outgoingÂ newsÂ andÂ watchingÂ theÂ newsÂ toÂ beÂ published (Solopos.comÂ editor)Â as well as overseeing the content of the news reporterwith editing directly.